The incidence of melanoma in South Africa: An exploratory analysis of National Cancer Registry data from 2005 to 2013 with a specific focus on melanoma in black Africans - Tod, B M; Kellett, P E; Singh, E; Visser, W I; Lombard, C J; Wright, C Y (South African medical journal = Suid-Afrikaanse tydskrif vir geneeskunde, 2019)
Melanoma is an aggressive skin cancer with poor survival when diagnosed late. There are important differences in clinical and histological features of melanoma and disease outcomes in people with darker skin types. A retrospective review of data captured by the National Cancer Registry (NCR) of South Africa (SA) was performed for 2005 - 2013. Data on patient numbers, demography, location and biological features were analysed for all records. Closer analysis of melanoma of the limbs reported in black Africans was done after manually collecting this information from original reports. With 11 784 invasive melanomas reported to the NCR, the overall incidence of melanoma for SA was 2.7 per 100 000. Males (51%), individuals aged ≥60 years (48%) and the anatomical sites of lower limb (36%) and trunk (27%) were most commonly affected. Melanoma incidences in the white and black populations were 23.2 and 0.5 per 100 000, respectively. Most cases were diagnosed at private pathology laboratories (73%). Superficial spreading melanoma (47%) and nodular melanoma (20%) predominated. Among 878 black Africans diagnosed in the public sector with melanoma of the limbs, females (68%) and individuals aged ≥60 years (61%) were most commonly affected. Lower-limb lesions (91%) and acral lentiginous melanoma (65%) predominated, with 74% of cases affecting the foot and 62% of cases presenting with a Breslow depth >4 mm. This study provides up-to-date NCR incidence and demographic data on melanoma and highlights the neglected research gaps in relation to melanoma in black Africans to provide evidence needed to address health disparities in overlooked population groups.